Business Process Reengineering pada Layanan Perpustakaan SMKN 13 Malang Menggunakan Uji Efisiensi Throughput - Rahmah, Anisa Ayu Nabila Nur; Suharso, Wildan (Prodi Sistem Informasi Universitas Dharma Andalas, 2026)
This study applies Business Process Reengineering (BPR) to improve the operational efficiency of the library at SMKN 13 Malang. The manual borrowing process was mapped and analyzed using Business Process Model and Notation (BPMN) and evaluated with the ASME-based throughput efficiency test. Data were collected through interviews and direct observation of library staff and activities. The initial borrowing process required 40,5 minutes with a throughput efficiency of only 62,96%, indicating long queues and a high risk of recording errors. The reengineered process introduces barcode-based automation for visitor identification and book lending, eliminating four non–value-added steps and automating two others. The redesigned workflow reduced the total borrowing time to 14,5 minutes and improved throughput efficiency to 100%. These results demonstrate that BPR significantly accelerates service delivery, reduces administrative burdens on staff, and enhances the overall user experience.